An Empire for Slavery : The Peculiar Institution in Texas, 1821-1865 - Campbell, Randolph B., 1940- (Book collections on Project MUSE., 1989)
In the popular mind, Texas conjures up images of the Old West and freedom of the range. Campbell reminds us that Texas grew from Southern roots entangled in human bondage. By the Civil War, Texas had a slave area equal to Alabama and Mississippi and a slave population comparable to Virginia. In the first comprehensive study of slavery in Texas, Campbell offers useful chapters on the law, the domestic slave trade, Indian relations, labor, family, religion, and more, but his book is especially welcome because it pulls the focus on bondage away from the Chesapeake and the Carolinas to show slavery's expansive and adaptive power in the developing West. Slavery knew no bounds, as Lincoln always understood. Recommended for college and university libraries.-- Randall M. Miller, St. Joseph's Univ., Philadelphia.